Maternal pre-eclampsia serum increases neurite growth and mitochondrial function through a potential IL-6-dependent mechanism in differentiated SH-SY5Y cells - Barron, Aaron; Manna, Samprikta; McElwain, Colm J.; Musumeci, Andrea; McCarthy, Fergus P.; O’Keeffe, Gerard W.; McCarthy, Cathal M. (Frontiers in Physiology, 2023)
Pre-eclampsia (PE) is a common and serious hypertensive disorder of pregnancy, which affects 3-5% of first-time pregnancies and is a leading cause of maternal and neonatal morbidity and mortality. Prenatal exposure to PE is associated with an increased risk of neurodevelopmental disorders in affected offspring, although the cellular and molecular basis of this increased risk is largely unknown. Here, we examined the effects of exposure to maternal serum from women with PE or a healthy uncomplicated pregnancy on the survival, neurite growth and mitochondrial function of neuronally differentiated human SH-SY5Y neuroblastoma cells, which are commonly used to study neurite growth. Neurite growth and mitochondrial function are two strongly linked neurodevelopmental parameters in which alterations have been implicated in neurodevelopmental disorders. Following this, we investigated the pleiotropic cytokine IL-6 levels as a potential mechanism. Cells exposed to 3% (v/v) PE serum for 72h exhibited increased neurite growth (p < 0.05), which was validated in the human neural progenitor cell line, ReNcell® VM (p < 0.01), and mitochondrial respiration (elevated oxygen consumption rate (p < 0.05), basal mitochondrial respiration, proton leak, and non-mitochondrial respiration) compared to control serum-treated cells. ELISA analysis showed elevations in maternal IL-6 in PE sera (p < 0.05) and placental explants (p < 0.05). In support of this, SH-SY5Y cells exposed to 3% (v/v) PE serum for 24h had increased phospho-STAT3 levels, which is a key intracellular mediator of IL-6 signalling (p < 0.05). Furthermore, treatment with anti-IL-6 neutralizing antibody blocked the effects of PE serum on neurite growth (p < 0.05), and exposure to IL-6 promoted neurite growth in SH-SY5Y cells (p < 0.01). Collectively these data show elevated serum levels of maternal IL-6 in PE, which increases neurite growth and mitochondrial function in SH-SY5Y cells. This rationalizes the further study of IL-6 as a potential mediator between PE exposure and neurodevelopmental outcome in the offspring.